Penerapan Metode EUCS terhadap Kepuasan Pengguna Sistem Informasi Akademik - Amin, M. Nur; Saputra, Eki; Hamzah, M. Luthfi; Rahmawita, Medyantiwi (Program Studi Teknik Informatika Universitas Pamulang, 2024)
In processing the student academic information system, an academic information system is needed on the Pelalawan Indonesia Plantation Technology Institute campus, which has been implemented since 2018. Since its implementation, there have still been several obstacles or problems experienced by users, such as repeated data entry when filling out lecturer and service performance questionnaires, menus that are not yet optimal. , menu structures that are difficult to understand and the need to add new menus, data processing that takes quite a long time and even errors occur. This research uses the EUCS method which aims to see the level of user satisfaction with the academic information system with a sample size of 75 people who are active students at the ITP2I campus. After conducting research, it was found that the level of user satisfaction with the academic information system was in the moderate range with a value of 0.648. Of the five hypotheses tested, two hypotheses were accepted. The two accepted hypotheses are that the Ease of Use and Format factors have a significant influence on user satisfaction. Meanwhile, three other hypotheses, namely Accuracy, Content and Timeliness, were rejected because they did not have a significant influence on user satisfaction.